2019
DOI: 10.1109/lmag.2019.2929484
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Barrier Nanomagnet Design for Binary Stochastic Neurons: Design Challenges for Real Nanomagnets With Fabrication Defects

Abstract: Much attention has been focused on the design of low barrier nanomagnets (LBM), whose magnetizations vary randomly in time owing to thermal noise, for use in binary stochastic neurons (BSN) which are hardware accelerators for machine learning. The performance of BSNs depend on two important parameters: the correlation time c associated with the random magnetization dynamics in a LBM, and the spin-polarized pinning current Ip which stabilizes the magnetization of a LBM in a chosen direction within a chosen tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…In the past, it was found that in magnetostrictive nanomagnets, strain-induced magnetization reversal (switching) probability is dramatically affected by the presence of defects 29,30 . Defects are also known to have a serious deleterious effect on the stochastic behavior of low energy barrier nanomagnets that have been proposed for use in stochastic computing 31 . Here, we have found that defects have a dramatic effect on spin wave modes as well.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, it was found that in magnetostrictive nanomagnets, strain-induced magnetization reversal (switching) probability is dramatically affected by the presence of defects 29,30 . Defects are also known to have a serious deleterious effect on the stochastic behavior of low energy barrier nanomagnets that have been proposed for use in stochastic computing 31 . Here, we have found that defects have a dramatic effect on spin wave modes as well.…”
Section: Resultsmentioning
confidence: 99%
“…All the non-ideal effects listed above are supposed to have minimal effects on different probability distributions shown in this article. Real LBMs may suffer from common fabrication defects, resulting in variations in average magnet fluctuation time τ N (Abeed and Bandyopadhyay, 2019 ). The autonomous BN is also quite tolerant to such variations in τ N as long as τ T ≪ min (τ N ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, for design 1 (Transistor-controlled) to function as a p-bit that has a step response time (τ step ) much smaller than its average fluctuation time (τ N ), the LBM fluctuation needs to be continuous and not bipolar. It is important to note that while most experimental implementations of low barrier magnetic tunnel junctions or spin-valves exhibit telegraphic (binary) fluctuations (Pufall et al, 2004 ; Locatelli et al, 2014 ; Parks et al, 2018 ; Debashis et al, 2020 ), theoretical results (Abeed and Bandyopadhyay, 2019 ; Hassan et al, 2019 ; Kaiser et al, 2019 ) indicate that it should be possible to design low barrier magnets with continuous fluctuations. Preliminary experimental results for such circular disk nanomagnets have been presented in Debashis et al ( 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Binary stochastic neurons (BSNs) are well suited to function as a 'spin' in Ising machines for solving combinatorial optimization problems 10,32 . A compact and efficient hardware realization of the BSN leveraging the natural physics of stochastic nanomagnets can be made by using unstable magnetic tunnel junctions (MTJs) [33][34][35][36][37] as shown in Fig. 1.…”
Section: General Approach To Design Of Bsnmentioning
confidence: 99%